AN ANALYSIS OF DIFFERENCES IN LEARNING OUTCOMES OF MANUFACTURING TECHNICAL DRAWING IN VOCATIONAL HIGH SCHOOLS IN SLEMAN REGENCY - suri, hesty monica; Ayuni Lestari; Insan Kamil (Jurnal Dinamika Vokasional Teknik Mesin, 2025)
This study aims to analyze the differences in learning outcomes of Manufacturing Technical Drawing among vocational high schools (SMK) in Sleman Regency, as well as to compare the specific achievements of public vocational schools (SMK Negeri).The study employed a quantitative descriptive method, involving 142 twelfth-grade students from the Mechanical Engineering program across five vocational schools: SMKN 1 Seyegan, SMKN 2 Depok, SMK Muhammadiyah Prambanan, SMK Nasional Berbah, and SMK Piri Sleman. Data were collected through a learning outcome test that assessed conceptual understanding, drawing skills, and proficiency in using design software. The results revealed significant differences in students' learning outcomes among the schools. SMKN 2 Depok achieved the highest average score (74.35), while SMK Piri Sleman recorded the lowest (65.29). A focused analysis of public vocational schools indicated that both SMKN 1 Seyegan (72.85) and SMKN 2 Depok (74.35) demonstrated high achievement levels, with a relatively small gap between their scores. Several factors contributed to these differences, including teacher competence, availability of facilities, teaching strategies, and student motivation. These findings are expected to provide valuable insights for schools to enhance the quality of teaching and learning.